The Technique of Phacoemulsification and Intraocular Lens Implantation in Subluxated Cataract Surgery - Huaiyan Jiang; Wenzhong Fu; Hongxia Xu (Stem Cells International)
The purpose of this study was to investigate the effectiveness and practicability of phacoemulsification and intraocular lens implantation for subluxated cataracts. A retrospective review of subluxated cataract surgeries of 19 eyes performed in Kunhua Hospital Affiliated with Kunming University of Science and Technology between January 2017 and June 2021 was conducted. We choose to use the rotate-and-chop phacoemulsification techniques described when the crystal nucleus is rotated out of the capsular bag and simultaneously perform horizontal chops over the capsule. The viscoelastic agent was the important material that filled the capsule to support the capsular bag, and capsular hooks were used in 10 eyes necessarily. Anterior vitrectomy was undergone in 15 eyes. Single-piece intraocular lenses (IOL) were implanted in the capsular bag in 12 eyes including 8 capsular tension ring (CTR) implantation. Three-piece IOLs were fixed scleral layer in 7 eyes. Follow-up was 6 months to 2 years, and all eyes were successfully implanted with centered IOL. The best corrected visual acuity (BCVA) increased from 0.06±0.04 to 0.62±0.15. The cornea of all patients was clear, the intraocular lens was centered, the pupil was round, and the intraocular pressure was normal. Subluxated cataracts are a challenging surgery. The technique of phacoemulsification in subluxated cataract surgery is a key procedure to rotate and remove the lens from the capsule and at the same time horizontal chops and emulsification over the capsular bag to be performed. Viscoelastic agents and capsular hooks were important choices to support the capsule to reduce the incidence of complications related to the vitreous and retina and prevent the range enlarging of the zonular dialysis. A capsular tension ring was also an effective device to maintain capsular stability. Double-needle-guided scleral interlamellar fixation is an effective and practical method for IOL. Overall, the incision technique explored in this study and the surgical technique to support capsular stabilization provide a safe approach and satisfactory results in cataract surgery for subluxation.